Characterization and transmission of plasmid-mediated multidrug resistance in foodborne Vibrio parahaemolyticus - Zhou, Haibo; Lu, Zhaoxin; Liu, Xinmei; Bie, Xiaomei; Cui, Xinping; Wang, Zuwei; Sun, Xiaojie; Yang, Jun (Frontiers in Microbiology, 2024)
Horizontal transmission of antimicrobial resistance genes (ARGs) mediated by mobile genetic elements is considered to be an important reason for the rapid development of resistance in Vibrio parahaemolyticus. Whole genome sequencing revealed that the multidrug-resistant V. parahaemolyticus strain NJIFDCVp52 contained two circular chromosomes and two circular plasmids (pVP52-1 and pVP52-2). Plasmid typing indicated that pVP52-1 belonged to the incompatibility group IncA/C2 and the sequence type pST3. pVP52-1 carried 12 different ARGs, an IS110-composite transposon consisting of aac(6')-Ib-cr, qnrVC1, aac(6')-Ib, dfrA14 and the IS26-mphA-IS6100 unit flanked by inverted sequences of IS5075 and IS4321. pVP52-2 carried no ARGs.A plasmid elimination assay showed that only pVP52-1 and its ARGs were lost, the loss of resistance to several antimicrobials, causing a change from the ampicillin-ampicillin/sulbactam-cefazolincefoxitin-ceftazidime-cefotaxime-imipenem-trimethoprim/ sulfamethoxazole resistance pattern to the ampicillin resistance pattern. In accordance, a conjugation transfer assay showed that only pVP52-1 and its ARGs were horizontally transferred, leading to increased antimicrobial resistance in Escherichia coli strain EC600, causing a change from the ampicillin-nalidixic acid resistance pattern to the ampicillin-ampicillin/sulbactam-cefazolin-cefoxitin-ceftazidime-cefotaxime-imipenemnalidixic acid-chloramphenicol-tetracycline-trimethoprim/sulfamethoxazole-azithromycin resistance pattern. Further transferability experiments revealed that pVP52-1 could be transferred to other enterobacterial strains of E. coli and Salmonella. Our findings provide more detailed information about ARG profiles and their transmission characteristics, suggesting the potential risk of the spread of multidrug resistance.